(3GdaGNQ aj GdWHs - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3Ef ef YXje fYe Gddg JYGdi Ydi YHGOg hLdjd HWhdg Ydi NdbI GdUMI ai OGA GdKYdH hgh JeQW GdTYQ s
(3BNQgG (B:s
(3hRfLHjd ef cd hGMO NeSI Ke SeGb YTQI Ke MH QeGf CMeQ Je GdLRA GdChd ef GdaGNQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs